Pengelolaan Keuangan pada TK Bunga Tanjung, Sarolangun - Ramlah, Fatmi (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2022)
An educational institution must be well managed in order to produce the expected results. There is often however misappropriation by individuals. In addition, the lack of institutions’ ability to obtain financial resources, the large operational expenditures of education and infrastructure and the non-transparency of financial information submitted to institutional supervisory get serious problems. This study aims to find out the picture of financial management in Bunga Tanjung Kindergarten, Sarolangun. This research uses a qualitative descriptive approach. The data was collected through a structured interview with the manager of Bunga Tanjung Kindergarten, Sarolangun. The data were analyzed using Miles and Huberman’s model, namely: data collection, data reduction, data presentation and drawing conclusions. The results showed that school finances were well managed as planned as budgets. This is shown by several activity plans that are realized as appropriate namely transparency, accountable, effective, and efficiency. The financial management in this school starts from planning, implementing, recording, accountability, and reporting.